BNT162b2-elicited neutralization of B.1.617 and other SARS-CoV-2 variants - Liu, Jianying; Liu, Yang; Xia, Hongjie; Zou, Jing; Weaver, Scott C.; Swanson, Kena A.; Cai, Hui; Cutler, Mark; Cooper, David; Muik, Alexander; Jansen, Kathrin U.; Sahin, Ugur; et al. (Nature (London), 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is continuing to evolve around the world, generating new variants that are of concern on the basis of their potential for altered transmissibility, pathogenicity, and coverage by vaccines and therapeutic agents 1 – 5 . Here we show that serum samples taken from twenty human volunteers, two or four weeks after their second dose of the BNT162b2 vaccine, neutralize engineered SARS-CoV-2 with a USA-WA1/2020 genetic background (a virus strain isolated in January 2020) and spike glycoproteins from the recently identified B.1.617.1, B.1.617.2, B.1.618 (all of which were first identified in India) or B.1.525 (first identified in Nigeria) lineages. Geometric mean plaque reduction neutralization titres against the variant viruses—particularly the B.1.617.1 variant—seemed to be lower than the titre against the USA-WA1/2020 virus, but all sera tested neutralized the variant viruses at titres of at least 1:40. The susceptibility of the variant strains to neutralization elicited by the BNT162b2 vaccine supports mass immunization as a central strategy to end the coronavirus disease 2019 (COVID-19) pandemic globally. Samples of serum from individuals immunized with the BNT162b2 vaccine show neutralization activity against engineered SARS-CoV-2s bearing the spike mutations from B.1.617 and other variants.